Marketing Mix in Service Affecting Strategic Image via Online Media: A Case Study of Bangkok Airways - เดชะพงศ์ธนา, กฤดิทัช; มีศิลปวิกกัย, กาญจนา (Siam Communication Review, 2019)
The study entitled ‘Marketing Mix In Service Affecting Strategic Image Via Online Media: A Case Study Of Bangkok Airways’ of which main objective is to study Bangkok Airways’ online media exposure affecting the company’s strategic image has promisingly found out the company’s marketing mix and its strategic image. Quantitative research methodology which consists of both open-ended and closed-ended questionnaires are provided is adopted for 400 targeted sample who used to receive Bangkok Airways’ service. Online media exposure is found to be at the moderate level. Information exposure is the highest, followed by searching the airline’s information via Facebook, learning promotional campaigns and activities via online media, and learning the passengers’ experience via online media that all are at high level. Average service marketing mix (7P) is found to be at high level. Distributional channels are at high level. Products’ taste and appropriate business class ticket price are at high level. User-friendly channels for ticket booking and payment through application and website are at high level. Promotions including special packages for the airline’s activities, cabin crews’ etiquette while on board, staff’s appropriate uniform, and flight punctuality are also at high level. Average strategic image is at the moderate level. Overall service image is at high level. When looking into details, the airlines standard, quality, and excellent executive board are all at high level